Flushing Out Carcinoid Syndrome: Beneficial Effect of the Anticancer Epigenetic Agent RRx-001 in a Patient with a Treatment-Refractory Neuroendocrine Tumor - Carter, Corey A. (Case Rep Oncol, 2015)
Neuroendocrine tumors (NET) are a heterogeneous group of neoplasms defined by the presence of cells with secretory granules and the potential to produce and release high levels of vasoactive peptides into the circulation, leading to severe flushing and diarrhea, which may adversely affect quality of life. This report presents the case of a 64-year-old man with chronic refractory diarrhea due to pulmonary NET treated with the experimental anticancer agent RRx-001 in a phase II trial called TRIPLE THREAT with subsequent resolution of his diarrhea.